Information management policy in Malaysian government research institutes / Abdul Rahman Ahmad - Ahmad, Abdul Rahman (2017)
Information policy is considered important components in regulating and controlling information related management and activities at organizational and national levels. However, literature and information from the fields indicate some degree of anonymity on its structure and roles. Although its conceptual aspects are described in numbers of literature, information policy components and other requirements necessary for the practical implementation of information management policy remain under-developed. This scenario could have been attributed to the lack of study in this area and, which has created voids in some methodological and theoretical aspects of information policy, particularly in relation to the management of information resources in organizations. To understand information management policy within organizational setting better, a two-case study strategy was adopted to provide collaborated views which, are more credible to answer research questions through the descriptions of roles played by information policy in regulating information management in the organizations, the organizational initiatives in supporting information management policy, roles and the critical resources for the development of information management policy. The framework of the study was established based on various conceptual components derived from various literature, three main dimensions are identified namely people resources, information system resources and information resources that influence information activities in the agencies (Orna, 1997). The approach was adopted because organizational information policy can be best understood from the manner it was operated in the actual environments. The current study takes the stand that in the absence of formal information policy does not necessarily mean that information policy is not practically available. Formal and informal initiatives adopted by organizations in managing their information resources, together with people and information technology resources, particularly on the creation, storage, use and dissemination of information should be examined to determine and to derive natures of information policy and how it has developed and impacted information management in organizations. These considerations become the parameter of the study and set information management policy framework consisting of elements that practically influence information activities and management in organizations. The 'lenses' must focus not only on the subsisting provisions of written information policy, also practices adopted by organizations, departments, and individuals to regulate, control, support or restrict information use and activities. Besides, the strategies and the implementation deployed by organizations using their available resources in managing their information resources are also important elements that illustrate the reality and information policy features in an organizational context which the current study must take into account. The research thus provides the understanding of important components of organizational information policy framework and critical resources that make information management policy practicable in organizations; identify lacuna and attritions in the acceptance, development, and implementation of organizational information policy and therefore remedies can be proposed to fill the gaps.